Impact of butyric acid modification on the structural and functional properties of rice starch - Qiaoyan Wu; Yang Yang; Yue Xu; Bing Wang; Xiaofei Liu; Yan Wang; Guang Zhang; Xin Bian; Chunmin Ma; Na Zhang (Current Research in Food Science)
Rice is a food with a high starch content, comprising over 75% of its composition. However, prolonged and excessive consumption of this cereal may lead to elevated blood glucose levels, which can increase the risk of obesity, type 2 diabetes, and cardiovascular disease. Butyric acid (BA), the primary energy source for colonic epithelial cells, exhibits the highest utilization rate among short-chain fatty acids, underscoring its importance for human health. In this study, rice starch butyrate (RSB) samples were synthesized using the aqueous phase process, with broken rice starch (RS) and butyric anhydride serving as the substrate. RSB samples with different degrees of substitution (DS) were produced by modulating the addition amount of butyric anhydride. The crystal structures, morphology of starch granules, pasting properties, thermal stability, and in vitro digestibilities of the RSB were investigated and compared with those of native rice starch. Fourier transform infrared (FTIR) spectroscopy confirmed the successful incorporation of butyryl into the starch molecules. With the increase in DS, the roughness of the RSB material's surface gradually increased, leading to the deterioration of the smooth structure on certain surfaces, which resulted in the appearance of cracks and collapses. Additionally, the crystallinity diminished from 24.77% to 7.41% with increasing DS. Concurrently, in vitro digestive characterisation revealed that the percentage of resistant starch increased from 24.33% to 47.72%. Thus, this study can provide a theoretical basis for the development of novel products of amyl butyrate.